Primary care colorectal cancer screening correlates with breast cancer screening: implications for colorectal cancer screening improvement interventions. Issue 4 (April 2018) - Weiss, Jennifer M.; Pandhi, Nancy; Kraft, Sally; Potvien, Aaron; Carayon, Pascale; Smith, Maureen A.
ABSTRACT : Objective: : National colorectal cancer (CRC) screening rates have plateaued. To optimize interventions targeting those unscreened, a better understanding is needed of how this preventive service fits in with multiple preventive and chronic care needs managed by primary care providers (PCPs). This study examines whether PCP practices of other preventive and chronic care needs correlate with CRC screening. Methods: : We performed a retrospective cohort study of 90 PCPs and 33, 137 CRC screening‐eligible patients. Five PCP quality metrics (breast cancer screening, cervical cancer screening, HgbA1c and LDL testing, and blood pressure control) were measured. A baseline correlation test was performed between these metrics and PCP CRC screening rates. Multivariable logistic regression with clustering at the clinic‐level estimated odds ratios and 95% confidence intervals for these PCP quality metrics, patient and PCP characteristics, and their relationship to CRC screening. Results: : PCP CRC screening rates have a strong correlation with breast cancer screening rates ( r = 0.7414, p < 0.001) and a weak correlation with the other quality metrics. In the final adjusted model, the only PCP quality metric that significantly predicted CRC screening was breast cancer screening (OR 1.25; 95% CI 1.11–1.42; p < 0.001). Conclusions: : PCP CRC screening rates are highly concordant with breast cancer screening. CRC screening is weakly concordant with cervical cancer screening and chronic disease management metrics. Efforts targeting PCPs to increase CRC screening rates could be bundled with breast cancer screening improvement interventions to increase their impact and success.